2018
DOI: 10.1007/s10803-018-3798-0
|View full text |Cite
|
Sign up to set email alerts
|

An International Survey of Parental Attitudes to Technology Use by Their Autistic Children at Home

Abstract: Capturing variability in use of commercial technologies by autistic children can inform future learning and support technology design. Survey data were collected from parents ( n = 388) in the UK, Spain, and Belgium, and includes information about individuals with a range of ages and ability levels. We found a comparable pattern of access and usage across age groups, though higher reading and language ability was linked to use of more devices and interfaces. Reported worries about techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…There is a lot of research highlighting that technology is a common interest among individuals with autism, including videogames (Laurie et al, 2019). The majority of the GD studies in the present review involved parental reporting of gaming behaviours as opposed to self-reports.…”
Section: Current Evidencementioning
confidence: 98%
See 1 more Smart Citation
“…There is a lot of research highlighting that technology is a common interest among individuals with autism, including videogames (Laurie et al, 2019). The majority of the GD studies in the present review involved parental reporting of gaming behaviours as opposed to self-reports.…”
Section: Current Evidencementioning
confidence: 98%
“…One recent study which administered the YIAT and CIUS to both parents and adolescents found that parents tend to overestimate GD and that self-reports were better aligned with the findings from clinical interviews (Yazdi et al, 2020). These findings may be exacerbated among autistic populations where gaming can be a special interest and parents can experience anxiety over their children's media use (Laurie et al, 2019). Some studies have found that parents have positive feelings towards media use among nonautistic samples (Vittrup et al, 2016).…”
Section: Current Evidencementioning
confidence: 99%
“…And the pervasive availability of tablets and smartphones, with touchscreen response and intuitive app development, means that most young people know how to interact with gamified tests, from their earliest years. As work by Laurie et al () shows, autistic children and adults across the full IQ range, interact with technology for much the same purposes, and with much the same preferences, as their neurotypical counterparts. These new technologies should lead to a revolution in research and herald the inclusion of intellectually impaired and minimally verbal children and adults in studies (e.g.…”
Section: The Changing Concept Of Autism: 1 From Narrow To Widementioning
confidence: 99%
“…Digital supports are defined as ‘any electronic item/equipment/application/or virtual network that is used intentionally to increase/maintain, and/or improve daily living, work/productivity, and recreation/leisure capabilities’ ( Odom et al, 2015 , p. 3806). In the past decade touchscreen, tangible and immersive digital technologies have become increasingly popular and accessible, with many autistic people and their parents/carers reporting high levels of digital technology use for supporting both leisure and academic pursuits ( Knight et al, 2013 ; Laurie et al, 2018 ; MacMullin et al, 2016 ; Pennington, 2010 ; Shane & Albert, 2008 ). Digital technologies have been developed to support autism in areas such as social skills and social interaction (for reviews see Camargo et al, 2014 ; Grossard et al, 2017 ; Ramdoss et al, 2011 ; Schlosser & Wendt, 2008 ) and emotion recognition (for review see Berggren et al, 2018 ).…”
mentioning
confidence: 99%